Pengembangan Produk Olahan Kopi sebagai Upaya Pemberdayaan Ekonomi Petani di Desa Karangpring Kabupaten Jember - Rengga, Virgilia Carolina; Wiryawan, Adhipramana Khansa; Putri, Frisca Teanna Adinda; Sayekti, Yosefa; Afkarina, R. Miftah; Ramadani, Pinky Fitria; Ilmi, Nilatul; Nasrullah, Ahmad Nadhif; Aziz, Nur Kholik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Indonesia is one of the largest coffee producers in the world, with Karangpring Village in Jember Regency as one of the areas producing quality coffee. Even though coffee production in this village is abundant, the economic conditions of the coffee farmers are still less prosperous because they only sell raw coffee beans at low prices. To overcome this problem, the Capacity Building Program (PPK) team from HMJA Jember University proposed a solution through downstream coffee products, namely by processing raw coffee beans into ground coffee. This step is expected to increase the selling value of products, farmers' income and their welfare. Service activities carried out include training in using tools, making ground coffee, forming business groups, as well as training on business strategies and product certification. With appropriate training and development support, it is hoped that coffee farmers in Karangpring Village can be independent and improve their welfare in a sustainable manner.